(untitled) (Al-Academy, 2024)
The current study entitled (the influence of heritage in the ceramic sculpture of the America Potter Paula Rice)The study is based on four chapters:Chapter I included structural find of clarification of the research problem and its importance, also included a mention of the research limits and the aim of this study, which is:-Identify sculptures Ceramic affected ranges for Potter Paula Rice civilization heritage of intellectual and artistic, whether global or local.-Trying to detect and intellectual influences the formalism of inherited and which resulted in the latest version of the unfinished ceramic artist.-Did the artist callback method to the values inherent succeeded in the embodiment of the meaning of originality according to the wording of the creative and compatible and contemporary taste. : Chapter II combine theoretical framework in three axes The first axis: heritageThe second axis: contemporary ceramic compositionThe third axis: the terms of reference of the American CeramicThis chapter also included mentions the most important indicators that resulted in her detective theory.Chapter III included search procedures and the method used in the descriptive analysis according to the axes learned analytical researcher.Chapter IV was to clarify the results learned by the researcher of the study samples and analysis results have been on the whole appear affected in the cultural historical legacy, the environment and the ideas contemporary philosophical and the modern art movements in addition of personal representation of individual self, which verify the concept of originality in art and then accommodate inherited values and put a new format made the concept of individual artistic identity for the Potter Paula Rice.